2018
DOI: 10.15171/ajmb.2018.07
|View full text |Cite
|
Sign up to set email alerts
|

Signaling in Simple Steatosis and Non-alcoholic Steatohepatitis Cirrhosis: TGF-β1, YAP/TAZ, and Hedgehog Pathway Activity

Abstract: Non-alcoholic fatty liver disease (NAFLD) refers to the accumulation of fat in the liver tissue that is usually associated with metabolic disorders. Traditionally, the disease is regarded as a spectrum of pathological conditions ranging from simple steatosis (SS) to non-alcoholic steatohepatitis (NASH) and hepatic fibrosis with progression to cirrhosis. However, so far, there is no available explanation for the disease progression. Several signaling pathways such as transforming growth factor (TGF)-β, hedg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Experimental studies demonstrated that the HH pathway ligand is overexpressed in non-alcoholic steatohepatitis (NASH) specimens. Additionally, it has been reported that the severity of liver disease is directly related to the activity of the SHH pathway in non-alcoholic fatty liver disease (19). However, studies on the liver tissue of patients with simple steatosis revealed that the SHH signaling pathway was downregulated in simple steatosis as compared to NASH-related cirrhosis (20).…”
mentioning
confidence: 99%
“…Experimental studies demonstrated that the HH pathway ligand is overexpressed in non-alcoholic steatohepatitis (NASH) specimens. Additionally, it has been reported that the severity of liver disease is directly related to the activity of the SHH pathway in non-alcoholic fatty liver disease (19). However, studies on the liver tissue of patients with simple steatosis revealed that the SHH signaling pathway was downregulated in simple steatosis as compared to NASH-related cirrhosis (20).…”
mentioning
confidence: 99%